Letter: repeat hepatic resection versus radiofrequency ablation for recurrent hepatocellular carcinoma in ideal candidates - authors' reply - Tong, Yao; Chang, De-Hua; Xiao, Yu-Dong (Alimentary pharmacology & therapeutics, 2023)
LINKED CONTENT This article is linked to Tong et al papers. To view these articles, visithttps://doi.org/10.1111/apt.17263 and https://doi.org/10.1111/apt.17409
Gesehen am 18.12.2023